Governing Indonesia’s Plan to Halt Bauxite Ore Exports: is Indonesia Ready to Fight Lawsuit at the WTO? - Aulawi, Muhamad Haris; Gunawan, Yordan; Alfarizi, M. Hanaan; Lago, Manuel Campos (BESTUUR, 2023)
Every nation has natural resources that must be regulated by state law and used for community benefit. Indonesia, a major exporter of bauxite ore to Europe, plans to ban exports. Indonesia must prepare for a second EU nickel ore export lawsuit after the first from the nickel export ban. The study aims to determine whether Indonesia is guilty of issuing a policy to stop exports of bauxite ore. This research is a normative legal research uses the rule of law, law principles, and legal doctrines to solve legal issues. Books, journals, and the internet provided data for the research. Articles from previous bilateral agreements are also used. This research examines Monism and Dualism.The results of the study show that Indonesia is not entirely at fault, considering that Indonesia is a country that adheres to a dualism system in international law enforcement. However, Indonesia still needs to renegotiate the percentage of bauxite ore exports with the European Union, considering that Indonesia is already bound by the IEU-CEPA agreement. If Indonesia continues its plan to stop the total export of bauxite ore, then Indonesia can still be considered to have committed acts of default.